Immobilisation of a Large Animal for Imaging Purposes - W. Szyszkowski (Applied Bionics and Biomechanics, 2010)
The mobility of a horse in the standing position with its hooves fixed to the ground is investigated to assist designing a minimally obstructing system for restraining large animals. The horse is modelled as a mechanical linkage driven by muscle forces. The linkage's configuration patterns, active joints and the forces associated with motion initiation are studied by reducing it to a mechanism with a low number of degrees of freedom. A restraint system blocking the motion of active joints with ropes is proposed as an alternative to massive mechanical devices restraining the whole body. The system has been verified experimentally on a sheep.